THE USE OF TROPICAL RAINFALL MEASURING MISSION RAINFALL DATA AS INPUT DATA FOR WATER AVAILABILITY ANALYSIS WITH RAINFALL-RUNOFF MODELS IN THE MELAWI SUB-BASIN - Gampo, Edi; Soeryamassoeka, SB; Kartini, Kartini (Fakultas Teknik Universitas Tanjungpura, 2023)
Many rain-to-discharge transformation models have been made, such as the Mock Model and the NRECA Model, which are used to make monthly synthetic discharge data when there is not enough discharge data to analyze water availability in a Sub-Basin or Sub-Basin. Tropical Rainfall Measuring Mission (TRMM) data, created by NASA and JAXA, is one type of satellite-based rainfall data that can help overcome the lack of rainfall data. However, not all areas have rainfall recording stations, and if there are, not all existing rainfall recording stations operate correctly. Such conditions also occur in the Melawi Sub-Basin in West Kalimantan. This research aims to determine how much water is available in the Melawi Sub-Basin by putting satellite-based rainfall data into the NRECA model and the Mock model, which converts rainfall to discharge.This study was done to determine how reliable TRMM satellite rainfall data are as input data for the rainfall-to-discharge transformation model used to determine how much water is available in the Melawi Sub-Basin. The goal of this study is to assess the suitability of TRMM data with observation station rainfall data in the Melawi Sub-Basin by validating TRMM satellite rainfall data with BMKG Susilo and BMKG Nanga Pinoh observation station rainfall data and to choose the appropriate rain-to-flow diversion model used in the Melawi Sub-Basin based on the results of model parameter calibration, with the models whose parameters are calibrated being the Mock Model and the NRECA.The study results show that TRMM rainfall data in the Melawi Sub-Basin that has been validated and corrected with the equation Y = 0.748089283 X + 62.19135368 can be used as input data in the analysis of water availability, and the transformation model of rainfall into discharge that is more suitable is the Mock Model. In general, both the observation station rainfall pattern and the TRMM rainfall pattern tend to have the same pattern as the discharge pattern in the Melawi Sub-Basin. The fact that August has the lowest peak is clear evidence of this. Even though the highest point doesn't happen in the same month, the trend is the same, so TRMM rainfall data can be considered valid and used to replace observational rainfall data in the Melawi Sub-Basin. Similar research can be done on other Sub-Basins in Kalimantan Barat Province to help develop and manage water resources since many observation stations in Kalimantan Barat Province no longer work, and there are many large Sub-Basins in that province.